Espacios universitarios de aprendizaje inclusivos, bilingües y multimodales: el caso del alumnado sordo signante - González-Montesino, Rayco Hautacuperche; Espada, Rosa M. (Journal of Learning Styles, 2020)
Achieving quality and inclusive education, which responds to the needs of all people, is still a challenge for our society today. The debate generated over decades about how to teach Deaf and hard of hearing students seems to be gradually fading away. The benefits of a bilingual education in which sign language plays a significant role are clearly demonstrated. However, creating inclusive learning spaces in universities for Deaf student’s sign language users has become a new challenge. In this paper, we present a case study in which we analyze the role that had the Spanish sign language as a vehicular language in the development of spaces (physical and virtual) fully inclusive, bilingual and multimodal. The results obtained from an in-depth interview with a Deaf student and from the survey of her classmates support the idea that an inclusive university education for Deaf people is possible.